The Oxford handbook of research strategies for clinical psychology - Comer, Jonathan S.; Kendall, Philip C. (Oxford library of psychology., 2013)
Mental health problems impose a staggering worldwide public health burden. Regrettably, whereas many sciences have been progressing for centuries (e.g., biology, chemistry) it is only recently that the strategies of science have been applied to the field of clinical psychology. At this relatively early stage in the science of clinical psychology, the majority of work is ahead of us, and as such the prepared investigator must be familiar with the full portfolio of modern research strategies-a set of 'directions' for getting from 'here' to 'there.' To continue to move the science of clinical psy.